Observation of auditory perceptual and visuo-spatial characteristic of a patient with hemangiopericytoma in occipital lobe: a magnetoencephalography (MEG) study - Hanani Abdul Manan; Jafri Malin Abdullah; Mohammed Faruque Reza; Muhammad Hafiz Hanafi; Zamzuri Idris (Penerbit Universiti Kebangsaan Malaysia, 2018)
The present study discussed functional reorganization and alteration in respond to the slow-growing tumour, hemangiopericytoma in the occipital cortex. Visual evoked field (VEF) and auditory evoked field (AEF) using magnetoencephalography (MEG) was used to evaluate the source localization and brain activity. Results of VEF source localization show a typical brain waves. Brain activity of the occipital lobe demonstrate low activation in the ipsilateral to the tumour. However, result shows the activation on the contralateral hemisphere was high and bigger in activation volume. AEF result shows an identical source localization and both side of the temporal lobe are activated. This result suggests that there is a positive plasticity in auditory cortex and slow-growing tumour can induce functional reorganization and alteration to the brain.